2001
DOI: 10.1128/jb.183.2.779-784.2001
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins Do Not Influence Wet Heat Resistance of Bacillus subtilis Spores

Abstract: Spores of Bacillus subtilis are significantly more resistant to wet heat than are their vegetative cell counterparts. Analysis of the effects of mutations in and the expression of fusions of a coding gene for a thermostable ␤-galactosidase to a number of heat shock genes has shown that heat shock proteins play no significant role in the wet heat resistance of B. subtilis spores.The gram-positive bacterium Bacillus subtilis undergoes the process of sporulation when nutrients become exhausted, and the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…However, the higher intrinsic thermostability of macromolecules, in particular proteins, from thermophiles also likely contributes to the increased wet heat resistance of their spores. In contrast to the situation in growing cells, heat shock proteins play no role in the wet resistance of spores (Melly and Setlow 2001).…”
Section: Heat Resistancementioning
confidence: 99%
“…However, the higher intrinsic thermostability of macromolecules, in particular proteins, from thermophiles also likely contributes to the increased wet heat resistance of their spores. In contrast to the situation in growing cells, heat shock proteins play no role in the wet resistance of spores (Melly and Setlow 2001).…”
Section: Heat Resistancementioning
confidence: 99%
“…In this study, KatA disappeared 2 h after acid shock was applied. It has also been shown that heat‐shock proteins do not directly influence wet heat resistance of B. subtilis spores, since analysis of the effects of mutations of heat‐shock genes did not produce differences in spore heat resistance (Melly and Setlow 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, KatA disappeared 2 h after acid shock was applied. It has also been shown that heat-shock proteins do not directly influence wet heat resistance of B. subtilis spores, since analysis of the effects of mutations of heat-shock genes did not produce differences in spore heat resistance (Melly and Setlow 2001). It is possible that sporulation was delayed by 1 h as a result of the 30 min of acid shock, but it is also possible that the induction of stress proteins for 30 min was responsible for the delay.…”
Section: Discussionmentioning
confidence: 99%
“…Heat treatment, UV, and ␥ radiation also exhibited promising decontamination properties against spores of Bacillus species. These reports have also indicated that, B. thuringiensis and B. anthracis Sterne along with B. cereus form a better group of surrogates for virulent B. anthracis [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 88%